2010
DOI: 10.1007/s00264-010-1113-6
|View full text |Cite
|
Sign up to set email alerts
|

In vivo behaviour of low-temperature calcium-deficient hydroxyapatite: comparison with deproteinised bovine bone

Abstract: This study aims to evaluate in detail the biological osteoconductive properties of the low-temperature synthetic porous calcium-deficient hydroxyapatite and to compare it with the biological apatite. Bone reactions to granules of similar sizes of the low-temperature hydroxyapatite and commercially available non-sintered deproteinized bovine bone were compared. Two different temperatures were used to fabricate two batches of newly developed porous hydroxyapatite with different carbonate groups content and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…Kozakiewicz et al [17], Ray et al [18], Merkx et al [19,20], Traini et al [21], Bashara et al [22], Jensen et al [23], Šponer et al [24], Cestari et al [25], report the possibility of using bone replacement materials of various types in diverse clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Kozakiewicz et al [17], Ray et al [18], Merkx et al [19,20], Traini et al [21], Bashara et al [22], Jensen et al [23], Šponer et al [24], Cestari et al [25], report the possibility of using bone replacement materials of various types in diverse clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…22 Recent studies have shown that n-CDHA at a lower Ca/P ratio (1.5-1.67) is more biologically active than the nano hydroxyapatite because the former has similar compositions and crystal structures to the mineral of nature bone. 23,24 The addition of MAC to n-CDHA results in an improvement in the mechanical strength and ductility. However, the granular form of n-CDHA-MAC renders it difficult to be applied in irregular, complex bone injuries.…”
Section: Discussionmentioning
confidence: 99%
“…13,29 Therefore, the incorporation of n-CDHA into the MAC matrix may improve the biological properties of the composite material and has positive effects on cell proliferation and viability. 24 ALP is an early marker for osteoblast differentiation and participates in the process of mineralization. 30 Our data showed that the ALP activity in MC3T3-E1 cells cultured on the n-CDHA/ MAC/CSH composite is significantly higher than in the cells cultured on pure CSH or control plates at 4 and 7 days of culture, indicating a promotion of osteogenesis by the n-CDHA/MAC/CSH composite.…”
Section: Discussionmentioning
confidence: 99%
“…Bone tissue engineering (TE) aims to regenerate and restore damaged or diseased bone by inducing the human body to heal itself using its intrinsic regenerative potential 1. Besides polymers or ceramic‐based biocompatible materials, either as single phases or composites,2–9 bone autografts, allografts, or xenografts have also been suggested as structural support (scaffolds) to repair or regenerate diseased bone 10–21. Advantages and disadvantages of decellularized bone for its use as TE scaffold have been discussed in the literature 11, 16–19…”
Section: Introductionmentioning
confidence: 99%
“…1 Besides polymers or ceramic-based biocompatible materials, either as single phases or composites, [2][3][4][5][6][7][8][9] bone autografts, allografts, or xenografts have also been suggested as structural support (scaffolds) to repair or regenerate diseased bone. [10][11][12][13][14][15][16][17][18][19][20][21] Advantages and disadvantages of decellularized bone for its use as TE scaffold have been discussed in the literature. 11,[16][17][18][19] Because of its three-dimensional (3D) microstructure and morphology (i.e., highly interconnected and permeable structure with high porosity), its natural nanoscale topography and hierarchical structure, biochemical composition, and suitable mechanical properties and structural environment, decellularized trabecular bone provides an adequate ''biomimetic'' scaffold/matrix that should enable cells to attach, proliferate, differentiate, and organize into healthy bone.…”
Section: Introductionmentioning
confidence: 99%